P-031 YI Segmental and Total Abdominal Colectomies are Safe Management Strategies for Colitis-Associated Neoplasia. (March 2016) - Cleveland, Noa Krugliak; Colman, Ruben; Rodriquez, Dylan; Hirsch, Ayal; Cohen, Russell; Hanauer, Stephen; Hurst, Roger; Hart, John; Rubin, David
Abstract : Background: The historical approach to dysplasia or adenocarcinoma in the setting of chronic colitis was to perform a total proctocolectomy due to concern of synchronous and metachronous neoplasia. However, advances in optical technology and dysplasia detection have enabled consideration of a modified approach to the management of patients after dysplasia is detected. We report our experience with segmental and total abdominal colectomies with surveillance follow-up in patients with Crohn's disease (CD) and ulcerative colitis (UC) who had pre-operative colonic neoplasia. Methods: This is a retrospective review from our tertiary IBD center of all patients who were found to have colitis-associated neoplasia on screening or surveillance colonoscopy and subsequently underwent segmental or total abdominal colectomy for this indication. Demographics and disease related information were collected. Pre-operative and surgical diagnoses of neoplasia were confirmed by expert gastrointestinal pathologists. Additionally, all surgical reports, as well as pre- and post-operative endoscopic reports were reviewed. Follow up was defined from the time of surgery (in months) until the last recorded endoscopic exam. Grade of neoplasia found during follow up was recorded. Simple statistical analysis was performed. Results: We identified 17 IBD patients who underwent segmental or total abdominal colectomy due to confirmed neoplasia (11 CD and 6 UC). The median age was 64 (range 40–78 years) with median disease duration of 20.5 years (range 5–46 years). The indications for surgery were low-grade dysplasia (LGD) in 11 patients (6 CD, 5 UC), high-grade dysplasia in 3 patients (2 CD, 1 UC) and adenocarcinoma in 3 patients (all CD). 5 patients (all UC) underwent total abdominal colectomy with ileo-rectal anastomosis and 12 underwent segmental colectomy (11 CD, 1 UC). The patients were followed for median of 17 months (range 3–228) with a median of 2 follow up endoscopic exams (range 1–8), most with high definition endoscopic equipment. In follow up, 4 patients (all CD) were found to have LGD; no cancers were identified during surveillance. Conclusions: We demonstrate the safety of segmental or total abdominal colectomy in patients with IBD undergoing surgery for neoplasia. In this series of patients, active surveillance of the retained large bowel using modern optical technology appears to be an effective management strategy. It is of interest that the only patients who had metachronous dysplasia were CD patients with larger segments of retained colon. We believe that segmental or subtotal colectomies can offer an improved quality of life without compromising cancer prevention strategies.